The Distribution of Target Ownership and the Division of Gains in Successful Takeovers. - Song, Moon H; Stulz, Rene M; Walkling, Ralph A (Journal of Finance, 1990)
This paper presents evidence that the distribution of target ownership is related to the division of the takeover gain between the target and the bidder for a sample of successful tender offers. In the whole sample, the target's gain is negatively related to bidder and institutional ownership. In the sample of multiple-bidder contests, the target's gain increases with managerial ownership and falls with institutional ownership.